Advances in Understanding Carbon Composite Catalysts Based on Cathode for Microbial Fuel Cells. Issue 11 (15th September 2021) - Li, Huiyu; Zhang, Xiuling; Liu, Yuanfeng; Wang, Jiaona; Lin, Xiaoqiu; Li, Congju
Abstract : Single‐chamber microbial fuel cells (MFCs) with a simple structure and superior performance have been extensively studied. However, due to the sluggish kinetics of the cathode oxygen reduction reaction (ORR), the power generation of MFCs is greatly constrained. It is highly desirable to explore efficient cathode catalysts for reducing the overpotential to improve the electrochemical performance of MFCs. To date, a considerable number of carbon‐based composites have exhibited comparable power generation capacity to Pt in MFCs, showing the great potential in the development of remarkable performance and low‐cost cathode ORR catalysts. Herein, recent achievements of carbon‐based composites of air‐cathodes based on single‐chamber MFCs are summarized, mainly focusing on the selection of carbon‐based materials, composite synthesis methods, and structural regulation on the nanoscale. The key factors affecting the ORR in composites are also discussed. The crucial challenges of MFCs that still need to be resolved are further summed up before practical applications and scale‐up fabrication. Particularly, this review focuses on the design strategies and preparation methods of functional carbon‐based composites to boost the performance of MFCs, aiming to provide some scientific directions to develop advanced materials for MFCs in the future. Abstract : Carbon‐based composite materials show excellent electrocatalytic performance in microbial fuel cells (MFCs). Their recent achievements based on MFC cathodes and the key factors affecting their electrocatalytic activity during the synthesis process are reviewed. Crucial challenges of MFCs that still need to be resolved are further summed up before practical applications and scale‐up fabrication.